1985
DOI: 10.1139/f85-130
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Stream Ecosystem Theory

Abstract: Four significant areas of thought, (1) the holistic approach, (2) the linkage between streams and their terrestrial setting, (3) material cycling in open systems, and (4) biotic interactions and integration of community ecology principles, have provided a basis for the further development of stream ecosystem theory. The River Continuum Concept (RCC) represents a synthesis of these ideas. Suggestions are made for clarifying, expanding, and refining the RCC to encompass broader spatial and temporal scales. Facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
270
0
17

Year Published

1990
1990
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 518 publications
(309 citation statements)
references
References 51 publications
16
270
0
17
Order By: Relevance
“…Nevertheless, there can be differences in abiotic and biotic aspects such as geomorphology, topography, chemistry and floral and faunal cornmunities. The strong linkage existing between strelms and their terrestrial surroundings is well established (Vannote et al 1980) and life-cycle, density, and biomass of stream macroinvertebrates are influenced by these variables (Vannote et al 1980, Gushing et al 1983, Minshall et al 1985. For instance growth rate and life cycle of some macroinvertebrates seem to be affected by food abundance (Cummins & Klug 1979) as well as food quality (Anderson & Cummins 1978, Ward & Cummins 1978.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there can be differences in abiotic and biotic aspects such as geomorphology, topography, chemistry and floral and faunal cornmunities. The strong linkage existing between strelms and their terrestrial surroundings is well established (Vannote et al 1980) and life-cycle, density, and biomass of stream macroinvertebrates are influenced by these variables (Vannote et al 1980, Gushing et al 1983, Minshall et al 1985. For instance growth rate and life cycle of some macroinvertebrates seem to be affected by food abundance (Cummins & Klug 1979) as well as food quality (Anderson & Cummins 1978, Ward & Cummins 1978.…”
Section: Introductionmentioning
confidence: 99%
“…The question of how the structure and function of communities change from headwaters to river mouths in relation to the abiotic environment remains a central issue in the study of the biology of running water systems ( Vannote et al 1980, Statzner & Higler 1985, Minshall et al 1985, Meyer & Edwards 1990, Wiley et al 1990, Petts & Calow 1996, Miranda & Raborn 2000, Maamri et al 2005. Several investigations of river zooplankton have shown that abundance and species richness increase downstream though the information available for large South American Rivers is limited (José de , Saunders & Lewis 1989, Vasquez & Rey 1989.…”
Section: Introductionmentioning
confidence: 99%
“…In the particular case of riparian, headwater wetlands, modifications in shoreline terrestrial vegetation to provide shading effects and allocthonous inputs of woody debris may facilitate the establishment of some benthic species through creation of more suitable habitat conditions (Vannote et al 1980, Minshall et al 1985. …”
Section: Resultsmentioning
confidence: 99%